2016
DOI: 10.1111/ropr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Science Use in Regulatory Impact Analysis: The Effects of Political Attention and Controversy

Abstract: Scholars, policymakers, and research sponsors have long sought to understand the conditions under which scientific research is used in the policymaking process. Recent research has identified a resource that can be used to trace the use of science across time and many policy domains. US federal agencies are mandated by executive order to justify all economically significant regulations by regulatory impact analyses (RIAs), in which they present evidence of the scientific underpinnings and consequences of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…An alternative interpretation of our findings is that EPA does not care very much at all about the public comments and rather just alters citations in RIAs to appease political elites and business interests. After all, a higher level of attention surrounding a rule by public commenters, interest groups, and the media does increase the amount of scientific citations invoked in an RIA (Costa et al, 2016), so we know rule-makers strategically respond to political controversy. This would suggest we are not uncovering influence per se, but merely reactiveness on the part of agency officials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative interpretation of our findings is that EPA does not care very much at all about the public comments and rather just alters citations in RIAs to appease political elites and business interests. After all, a higher level of attention surrounding a rule by public commenters, interest groups, and the media does increase the amount of scientific citations invoked in an RIA (Costa et al, 2016), so we know rule-makers strategically respond to political controversy. This would suggest we are not uncovering influence per se, but merely reactiveness on the part of agency officials.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on research cited in RIAs as concrete pieces of evidence that are drawn upon in the regulatory policymaking process. This follows recent work by Desmarais and Hird (2014), Witting (2015), and Costa et al, (2016), in which bibliometric analysis of policy documents is used to precisely connect public policy outcomes to scientific evidence. We ask whether comments on the research cited in an RIA result in revisions to successive RIAs.…”
Section: The Use Of Informationmentioning
confidence: 95%
“…Recent examples of such use can be seen when actors opposing climate change mitigation search for particular studies purporting to show that climate change is not happening or is not due to human actions (Hansson, ; Sarewitz, ). Researchers have found that use of science to justify agency regulations is positively correlated with the saliency of the regulations to the public and other policy actors (Costa, Desmarais, & Hird, ). Kropp and Wagner () conclude that the use of science to justify prior decisions (symbolic use) is more prevalent at one particular stage of the policy process, the decision stage.…”
Section: Use Of Science In Collaborative Planning and Government Polimentioning
confidence: 99%
“…Participants are more likely to influence policy through comment processes when they provide useful, substantive information, especially at the early stages of regulatory decision making (Naughton et al 2009;Costa, Desmarais, and Hird 2016). A better understanding of the commenters and the arguments they offered during the public comment process might provide insight into how the new policy is working and the extent to which consulting the public influences CMS approval of the waivers.…”
Section: Role Of Low-income Citizens In Medicaid Policy Makingmentioning
confidence: 99%